2020
DOI: 10.21873/invivo.12103
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Impact of the Age-adjusted Charlson Comorbidity Index on Esophageal Cancer Patients Who Receive Curative Treatment

Abstract: Background/Aim: We investigated the impact of the age-adjusted Charlson comorbidity index (ACCI) on esophageal cancer survival and recurrence after curative treatment. Patients and Methods: This study included 122 patients who underwent curative surgery followed by adjuvant chemotherapy for esophageal cancer between 2005 and 2017. The risk factors for the overall survival (OS) and recurrencefree survival (RFS) were identified. Results: An ACCI of 5 was regarded as the optimal critical point of classification c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…Each decade over the age of 40 years was assigned a comorbidity score of 1. ACCI was calculated by adding the CCI score and age, where a higher score indicated a poorer physical condition ( Aoyama et al, 2020 ). Since all patients were 60 years old or over, ACCI score was not less than 2 points ( Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each decade over the age of 40 years was assigned a comorbidity score of 1. ACCI was calculated by adding the CCI score and age, where a higher score indicated a poorer physical condition ( Aoyama et al, 2020 ). Since all patients were 60 years old or over, ACCI score was not less than 2 points ( Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis has demonstrated that CCI ≥ 2 was independently associated with the development of POD ( Mevorach et al, 2022 ). After adjusting age as a correction variable, Age-adjusted Charlson Comorbidity Index (ACCI) is regarded as a new index to evaluate prognosis, which is calculated ultimately by integrating age and all underlying diseases, namely, cerebrovascular disease, liver or kidney disease, and heart disease, etc., and a higher ACCI can lead to worse survival rate and more mortality ( Aoyama et al, 2020 ). Currently, ACCI is applied to standardize the evaluation of surgical patients and to predict the post-operative mortality of patients undergoing surgery ( Asano et al, 2017 ; González Quevedo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even the first-stage patients received postoperative adjuvant therapy on request, resulting in a potential selection bias. Patients with esophageal cancer often have comorbidities such as chronic obstructive pulmonary disease and liver dysfunction as well as physiological problems that can cause greater drug toxicity than that in patients with other cancers [ 29 , 30 ]. Therefore, it is important to determine the clinical predictors of serious adverse events and early discontinuation of S-1 adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Anticipation of this treatment can lead to or aggravate emotional distress associated with significant sleep disorders. This is mainly due to concerns regarding the upcoming aggressive treatment, which is associated with severe side effects in the majority of the patients (6)(7)(8)(9)(10)(11)(12). Moreover, pre-treatment sleep disorders were reported to be associated with sleep disturbance after esophagectomy (13) course of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%